2018
DOI: 10.1101/257311
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Trans-ancestral GWAS of alcohol dependence reveals common genetic underpinnings with psychiatric disorders

Abstract: 94 35 NIH/NIAAA, Office of the Clinical Director 95 ABSTRACT 180Liability to alcohol dependence (AD) is heritable, but little is known about its complex 181 polygenic architecture or its genetic relationship with other disorders. To discover loci 182 associated with AD and characterize the relationship between AD and other psychiatric 183 and behavioral outcomes, we carried out the largest GWAS to date of DSM-IV 184

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
66
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 36 publications
(67 citation statements)
references
References 59 publications
1
66
0
Order By: Relevance
“…A recent large GWAS meta-analysis of 14 904 AD cases and 37 944 controls, which includes some of the samples used in this study, also only detected genome-wide significant (GWS) association with rs1229984 (Europeans) and rs2066702 (African-Americans); both single nucleotide polymorphism (SNP) are in ADH1B. 6 However, when examining a broader definition of alcohol use disorders from medical records, loci in additional genes have recently been identified. 4 We have previously conducted GWAS of AD-related phenotypes in smaller subsets of the data used in the present study, but results have eluded replication and power to detect rs1229984 has been low (eg, for AD in a subset of 1884 unrelateds, 7 for AD, criterion count and criteria in 2010 to 2322 individuals from 118 families 8,9 ).…”
Section: Introductionmentioning
confidence: 75%
See 3 more Smart Citations
“…A recent large GWAS meta-analysis of 14 904 AD cases and 37 944 controls, which includes some of the samples used in this study, also only detected genome-wide significant (GWS) association with rs1229984 (Europeans) and rs2066702 (African-Americans); both single nucleotide polymorphism (SNP) are in ADH1B. 6 However, when examining a broader definition of alcohol use disorders from medical records, loci in additional genes have recently been identified. 4 We have previously conducted GWAS of AD-related phenotypes in smaller subsets of the data used in the present study, but results have eluded replication and power to detect rs1229984 has been low (eg, for AD in a subset of 1884 unrelateds, 7 for AD, criterion count and criteria in 2010 to 2322 individuals from 118 families 8,9 ).…”
Section: Introductionmentioning
confidence: 75%
“…Despite the robust relationship between this functional variant and AD, its relatively low minor allele frequency necessitates fairly large samples to detect a GWS effect for a binary trait, as was shown in a recent metaanalysis of DSM-IV AD. 6 However, for DSM-IV AD criterion count, rs1229984 was GWS in both the EA and EA + AA analyses. Similar to another study, 16 we found that while rs1229984 was associated with each individual criterion (EA all P < 3.61E−04; EA + AA all P < 4.54E…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…For example, it could be that that the combination of an early onset in adolescence and persistent course of AUD has the strongest effect on midfrontal theta in adulthood. Finally, findings from a recent large-scale genome-wide association study of alcohol dependence suggest that pathological alcohol use and measures of normative alcohol consumption are only modestly genetically correlated (Walters et al, 2018). As the liability underlying clinically problematic alcohol use (e.g., AUD) and phenotypes of normative drinking patterns (such as those used in our previous report; Harper et al, 2017a) only partially overlap, it is not clear whether our prior theta-adolescent drinking findings will extend to AUD measures.…”
Section: Introductionmentioning
confidence: 99%